2018
DOI: 10.1021/jacs.8b09842
|View full text |Cite
|
Sign up to set email alerts
|

Lanmodulin: A Highly Selective Lanthanide-Binding Protein from a Lanthanide-Utilizing Bacterium

Abstract: Lanthanides (Lns) have been shown recently to be essential cofactors in certain enzymes in methylotrophic bacteria. Here we identify in the model methylotroph, Methylobacterium extorquens, a highly selective LnIII-binding protein, which we name lanmodulin (LanM). LanM possesses four metal-binding EF hand motifs, commonly associated with CaII-binding proteins. In contrast to other EF hand-containing proteins, however, LanM undergoes a large conformational change from a largely disordered state to a compact, ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
423
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(450 citation statements)
references
References 37 publications
17
423
1
9
Order By: Relevance
“…Recently, we demonstrated, using a genetically encoded fluorescent sensor for lanthanides, that only light lanthanides, La–Nd, are efficiently imported into the bacterial cytosol, a process likely facilitated by a secreted metallophore . Therefore, it appears that on multiple levels—including, at least, regulation, uptake, and trafficking,— M. extorquens is fine‐tuned to use solely light lanthanides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated, using a genetically encoded fluorescent sensor for lanthanides, that only light lanthanides, La–Nd, are efficiently imported into the bacterial cytosol, a process likely facilitated by a secreted metallophore . Therefore, it appears that on multiple levels—including, at least, regulation, uptake, and trafficking,— M. extorquens is fine‐tuned to use solely light lanthanides.…”
Section: Introductionmentioning
confidence: 99%
“…[7a, 9] In addition, some XoxF-MDHsa re able to oxidise formaldehydet of ormate. [13] Further,V orholt et al reported that in the uptake of Ln by M. extorquens aT onB related transporter is likely to be involved. [7a, 11] At hird crystal structure of the La 3 + derivative of the MDH from Methylomicrobium buryatense 5GB1C was reported in 2018 by Rosenzweig and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…[9, 14e] Bakterien mit beiden Genen, wie M. extorquens AM1, exprimieren Ln-MDH, wenn die Lanthanoid-Konzentration ausreichend hoch ist (Abbildung 1). [19] LanM verfügt über drei carboxylatreiche Metallbindungsstellen (EF hands), die Ln mit picomolarer Affinität binden, und eine weitere,d ie mit mikromolarer Affinität bindet. [16] Diese Flexibilitätw ird als "lanthanide switch" bezeichnet.…”
Section: Die Bedeutung Von Lanthanoiden In Der Mikrobiologieunclassified
“…Martinez-Gomez, Skovran und Mitarbeiter konnten zeigen, dass eine Konzentration von 2.5 nm La ausreichte,u mxoxF-Expression zu aktivieren, während geringe Konzentrationen wie 25 nm genügten, um mxaF-Transkription zumindest teilweise zu unterbinden. [19] Eine NMR-Strukturanalyse von Lanmodulin ist verfügbar (Abbildung 2). Ein solches Umschalten zwischen Stoffwechselwegen und veränderte Genexpression bei Abwesenheit oder Vorhandensein bestimmter Elemente ist ein bekanntes Konzept fürd en Methanoxidationsschritt in Bakterien.…”
Section: Die Bedeutung Von Lanthanoiden In Der Mikrobiologieunclassified
See 1 more Smart Citation